Software Engineering for Resilient Systems 4th International Workshop, SERENE 2012, Pisa, Italy, September 27-28, 2012. Proceedings - Avgeriou, Paris; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the Fourth International Workshop on Software Engineering for Resilient Systems, SERENE 2012, held in Pisa, Italy, in September 2012. The 12 revised full papers were carefully reviewed and selected from numerous submissions. The papers address all aspects of fault tolerance and exception handling, safety modeling, supporting evolution, resilience in service-oriented computing, and applying formal methods in case studies.
Keywords: Computer science; Computer Communication Networks; Software engineering; Operating systems (Computers).; Computer Science; Software Engineering; Computer Communication Networks; Information Systems Applications (incl. Internet).; Operating Systems